Knowledge-practice gap in breastfeeding and the factors influencing it among the urban mothers attending the immunization clinic under a tertiary care hospital in eastern India - Kar, Sonali; Singh, Snigdha; Kar, Ansuman (International Journal Of Community Medicine And Public Health, 2023)
Background: Breast milk is a complete food for the newborn. Timely introduction of breast milk and exclusive breast feeding till 6 months of age of a newborn, with proper positioning and adequate attachment to mother’s breast is encouraged as Initiation of breast feeding within the first hour after birth, prevents the newborn from the risk of morbidity and mortality. An effective improvement in mother’s self efficacy and understanding on breast feeding will be useful in meeting the nutritional goals of the child. Aim of study was to assess the knowledge, perception and practice among the mothers on breast feeding and the factors influencing their practice and to determine probable association of ideal infant weight with exclusive breast feeding. Methods: Descriptive cross-sectional study among 390 mothers attending the Immunization Clinic of Kalinga Institute of Medical Sciences, Bhubaneswar. They were assessed if they breast fed infant by following the ideal positioning and proper attachment to breast and for their knowledge, perception and practices of breast feeding. Analysis was done using STATA-17. Results: Good knowledge, perception and practice of breast feeding was present among 88.2%, 83.5% and 69.8% mothers, respectively. Association between ideal weight of baby and proper breast feeding technique was found. Knowledge was more positively related to practice, than to perception. Conclusions: Children who have been exclusively breast fed, had the right weight for age. Mother and other family members must be aware of proper technique, adequacy and frequency of breast feeding for the best nourishment of the newborn.